Immediate Surgery Might Be a Better Option for Subcapsular Thyroid Microcarcinomas - Jun Jiang; Hui Lu (International Journal of Endocrinology)
For high-risk papillary thyroid microcarcinomas (PTMCs), immediate surgery is recommended. This study aimed to evaluate the location of PTMCs in the thyroid lobe and determine whether location is associated with an aggressive biology and the necessity of immediate surgery. This retrospective study included 288 patients who underwent initial surgery for PTMC. Clinical data were extracted. Subcapsular thyroid microcarcinomas (STMs) and nonsubcapsular thyroid microcarcinomas (NSTMs), distinguished by ultrasound, were compared in terms of tumour size, extrathyroidal extension, cervical lymph node metastasis, and multifocality. The preoperative ultrasound features predictive of recurrent laryngeal nerve (RLN) involvement were assessed. There were no statistical differences in tumour size (P = 0.985), multifocality (P = 0.866), lymph node metastases to the central compartment (P = 0.154), or lateral lymph node metastases (P = 0.929) between STM and NSTM groups. Macroscopic extrathyroidal extension was exclusively found in the STM group. For assessing RLN involvement, the sensitivity, specificity, and positive predictive value of the presence of an abnormal thyroid capsule margin between the STM and the presumed RLN course, assessed on preoperative ultrasonography images, were 100%, 43.3%, and 43.3%, respectively. Immediate surgery appears to be a better option than conservative treatment for these high-risk STM patients.